Pengaruh Pengetahuan Finansial dan Jenis Kelamin terhadap Perilaku Keuangan Mahasiswa FKIP UNS - Listyoningrum, Kus Indrani; Susilaningsih, Susilaningsih (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2025)
This study aims to examine how financial knowledge and gender affect the financial behavior of FKIP UNS students. Using a descriptive quantitative approach with a survey method, the research focuses on sixth- and eighth-semester students from the Accounting Education, Office Administration Education, and Economic Education programs. A purposive sampling method was applied, resulting in a sample of 221 students. Data were gathered through questionnaires and analyzed using descriptive statistics, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). Additionally, normality, linearity, and multicollinearity tests were conducted as prerequisites. The results highlight three main findings: (1) Financial knowledge has a significant impact on financial behavior, evidenced by a t-test significance of 0.013 (p < 0.05); (2) Gender also significantly influences financial behavior, with a t-test significance of 0.038 (p < 0.05); (3) Combined, financial knowledge and gender significantly affect financial behaviour, supported by an F-test significance of 0.007 (p < 0.05).